2022
DOI: 10.35335/midwifery.v11i1.582
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self Help Groups on the Self Efficacy of People with Type 2 Diabetes Mellitus at the Paccerakkang Health Center in Makassar City

Abstract: Optimal self-efficacy is a key factor in the success of self-management of DM patients. Poor self-efficacy affects many things, such as motivation and adherence, and can lead to poor self-care management by people affected by DM. Learning from the experiences of others through the law of self-help groups can increase self-efficacy.The purpose of this study was to clarify the influence of self-help groups on the self-efficacy of type 2 diabetes patients at the Paccerakkang Health Center in Makassar City. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…There is a significant difference in self-efficacy between groups that are given self help group and those that are not in this study, in line with the results of research conducted by Syaipuddin et al, (2022), where in this study the results obtained were that there was an effect of self help group on sufferers' self-efficacy in DM Type 2 with a p value of 0.000. Learning from the experiences of others obtained in a selfhelp group is a source for increasing self-efficacy; observing the success of other people who have the same problems will increase self-efficacy in solving problems experienced (Syaipuddin et al, 2022). This means that establishing selfhelp groups for gouty arthritis patients can boost their selfefficacy.…”
Section: Resultssupporting
confidence: 90%
“…There is a significant difference in self-efficacy between groups that are given self help group and those that are not in this study, in line with the results of research conducted by Syaipuddin et al, (2022), where in this study the results obtained were that there was an effect of self help group on sufferers' self-efficacy in DM Type 2 with a p value of 0.000. Learning from the experiences of others obtained in a selfhelp group is a source for increasing self-efficacy; observing the success of other people who have the same problems will increase self-efficacy in solving problems experienced (Syaipuddin et al, 2022). This means that establishing selfhelp groups for gouty arthritis patients can boost their selfefficacy.…”
Section: Resultssupporting
confidence: 90%
“…Diabetic foot exercise was also one of therapy that may improve blood glucose regulations. This proved by several studies that found blood glucose level gradually decreased after getting this exercise (Graciella & Prabawati, 2020;Haskas et al, 2023). This better regulation of blood glucose then improve wound healing process among patients (Pasaribu & Sebayang, 2020) An interesting aspect of providing diabetes foot exercises is that they not only provide physical benefits but also offer psychological benefits related to comfort during religious rituals.…”
Section: Outcomes Of Diabetic Foot Exercisesmentioning
confidence: 95%
“…Latihan senam diabetik ini merupakan salah satu jalan untuk mengatasi gangguan sensitivitas pada kaki bagi penderita diabetes melitus. Maka Latihan senam diabetik ini sangat mempengaruhi untuk menurunkan kadar gula darah dan meningkatkan sensitivitas kaki pada pasien DM dengan melakukan gerakan kesepuluh [30].…”
Section: Pembahasanunclassified